2011
DOI: 10.1159/000334071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Monounsaturated Fatty Acids on Cardiovascular Risk Factors: A Systematic Review and Meta-Analysis

Abstract: The appropriate pattern of macronutrient distribution for dietary protocols aimed at treating or preventing obesity and its associated cardiovascular diseases is still a controversial topic of discussion. Recommendations considering a specific percentage or range for monounsaturated fatty acids (MUFA) are rare. It was the aim of this study to analyze long-term, randomized, controlled dietary intervention trials and to investigate the effects of MUFA on the biomarkers of obesity and cardiovascular risk factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 90 publications
5
86
0
1
Order By: Relevance
“…High-MUFA regimes seem to have a significantly more pronounced impact on fat mass than on total weight. 11 The results of this national, crosssectional study show that obese persons and persons with a carbohydrate metabolism disorder generally consumed less olive oil and that persons who consumed olive oil tended to have a lower prevalence of obesity and type 2 diabetes mellitus, supporting the hypothesis of a lower risk for obesity and type 2 diabetes mellitus in persons who consume olive oil, as found in several prospective studies 32,33 and in a recent clinical trial in persons at high risk for cardiovascular disease. 34 Of particular note was the association found between olive oil consumption and the population pattern of insulin resistance.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…High-MUFA regimes seem to have a significantly more pronounced impact on fat mass than on total weight. 11 The results of this national, crosssectional study show that obese persons and persons with a carbohydrate metabolism disorder generally consumed less olive oil and that persons who consumed olive oil tended to have a lower prevalence of obesity and type 2 diabetes mellitus, supporting the hypothesis of a lower risk for obesity and type 2 diabetes mellitus in persons who consume olive oil, as found in several prospective studies 32,33 and in a recent clinical trial in persons at high risk for cardiovascular disease. 34 Of particular note was the association found between olive oil consumption and the population pattern of insulin resistance.…”
Section: Discussionsupporting
confidence: 68%
“…22 The relations between the type of dietary fat, plasma lipid levels and cardiovascular risk have repeatedly been confirmed in experimental as well as clinical and epidemiological studies. 11 Low-fat diets usually reduce both LDL cholesterol and HDL cholesterol. [23][24][25] The replacement of carbohydrates by dietary fats reduces triglyceride levels and increases HDL cholesterol, [26][27][28] whereas the substitution of saturated fats by monounsaturated fats decreases levels of LDL cholesterol 27 or at least does not change them 28,3 but increases levels of HDL cholesterol 26,28 In our study, persons who consumed olive oil had lower values of triglycerides and slightly higher (but nonsignificant) levels of LDL cholesterol, and both men and women had higher levels of HDL cholesterol, with a significantly lower probability of having low HDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two additional meta-analyses of randomized clinical trials and cohort studies also reported the beneficial effects of MUFA-rich diets on the reduction of CVD, although these findings were not conclusive 37,38 .…”
Section: Monounsaturated Fatty Acids and The Prevention Of Cardiovascmentioning
confidence: 99%